Efficiency Play, Games, Competitions, Production - How to Analyze the Configurations of Sport? - Eichberg Henning (Sciendo, 2016)
The comparative, differential phenomenology of play and games has a critical political point. A mainstream discourse identifies - more or less - sport with play and game and describes sport as just a modernized extension of play or as a universal phenomenon that has existed since the Stone Age or the ancient Greek Olympics. This may be problematical, as there was no sport before industrial modernity. Before 1800, people were involved in a richness of play and games, competitions, festivities, and dances, which to large extent have disappeared or were marginalized, suppressed, and replaced by sport. The established rhetoric of "ancient Greek sport", "medieval tournament sport", etc., can be questioned.